Design guidelines for slanting silicon nanowire arrays for solar cell application - Hong, Lei (2013)
The reflectance and absorption characteristics of slanting silicon nanowires (SiNWs) structure have been simulated using finite element method to provide a design guideline for its application in solar cell. The slanting angle for the nanowire structure is set at 40° on Si (111) wafer. The impact of the structural periodicity (P) and wire diameter/periodicity (D/P) ratio on the optical characteristics of the slanting SiNW has been systematically analyzed. It has been found that due to the much suppressed light reflection and stronger light trapping ability, the light absorption is significantly enhanced for the slanting SiNW structure compared with vertical SiNW structure. The optimal absorption condition is achieved when P = 800 nm and D/P = 0.7, yielding the highest ultimate efficiency of 33.45%. The result is better than the 28.36% that can be achieved for optimum vertical SiNWs. A comparison of the absorption characteristics of optimum slanting and vertical SiNWs structures is presented and analyzed in terms of the physical light interaction with the structures.